2011
DOI: 10.1515/jpm.2011.044
|View full text |Cite
|
Sign up to set email alerts
|

Fetal outcome for infants in breech by method of delivery: experiences with a stand-by service system of senior obstetricians and women's choices of mode of delivery

Abstract: Vaginal breech delivery is a safe option in a stand-by system of senior obstetricians with controlled decision-making before labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…When infants with congenital malformations were excluded, they reported no perinatal deaths in their material. This is in line with the conclusions of an Austrian observation study comprising 211 breech presentation pregnancies where 46 of 85 planned vaginal deliveries actually went vaginally [22]. Common features of the French/Belgium, the Finnish, the Austrian and our study, include strict selection criteria for whom should be offered vaginal delivery, close fetal monitoring and the presence of skilled obstetricians.…”
Section: Discussionsupporting
confidence: 90%
“…When infants with congenital malformations were excluded, they reported no perinatal deaths in their material. This is in line with the conclusions of an Austrian observation study comprising 211 breech presentation pregnancies where 46 of 85 planned vaginal deliveries actually went vaginally [22]. Common features of the French/Belgium, the Finnish, the Austrian and our study, include strict selection criteria for whom should be offered vaginal delivery, close fetal monitoring and the presence of skilled obstetricians.…”
Section: Discussionsupporting
confidence: 90%
“…A number of registry‐based studies have shown a significant increase in cesarean delivery rates and a simultaneously decrease in neonatal mortality and morbidity when comparing the years before and after the TBT publication in October 2000 . On the other hand, several cross‐sectional and prospective observational studies have reported no significant difference in neonatal morbidity between PVD and PCD when applying predefined selection criteria for mode of delivery . However, most of these studies were not powered for detecting differences in neonatal mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Breech presentation occurs in about 3–4 percent of term deliveries . In the absence of an absolute indication for cesarean section (CS), the optimal mode of delivery remains controversial, as studies both encouraging and discouraging a trial of vaginal delivery have been published . In Finland, in the case of a normal pregnancy and lack of medical contraindications, a trial of vaginal birth is an option if strict selection criteria are met.…”
Section: Introductionmentioning
confidence: 99%